Implementation of child protection in the UAE under Khalifa bin Zayed Al-Nahyan: A policy analysis of the children's safety framework - Muhammad Fajhriyadi Hastira; Ronel Jhon Lumor Guarte; Chaliza (Department of Government Science, 2026)
The United Arab Emirates (UAE), despite operating under a royal system of government, has pursued significant advancements in children's rights. This paper employs a qualitative descriptive design to examine child protection implementation in the UAE during the leadership of Khalifa bin Zayed Al Nahyan, analyzing key legal instruments, particularly Federal Law No. 3 of 2016 (Wadeema's Law), and institutional programs under the Children's Safety framework, including the Child Protection Unit, Child Protection Committee and Centre, and Child Safety Department. Using Rosenau's political behavior framework, the study analyzes how leadership personality and executive authority have shaped child protection policy. Findings indicate measurable progress in specific domains, particularly health and protection, as reflected in successive KidsRights Index editions, while persistent gaps remain in the structural conditions necessary for comprehensive realization of children's rights, most notably in the enabling environment domain. This study offers comparative insights for countries, particularly those in the Middle East, seeking to strengthen child protection policies while navigating the intersection of international human rights standards and domestic legal traditions.